Construction of Endometrial Carcinoma ceRNA Network and Screening of Key Genes Based on TCGA Database. (4th July 2022) - Song, Yuchun; Chu, Ping; Li, Pan; Li, Fengling
Abstract : Objective . Long noncoding RNA (lncRNA) has received more and more attention in human tumor research. This study is aimed at clarifying the regulatory network of lncRNAs-microRNAs- (miRNAs-) mRNAs and at determining the relevant targets in the development of endometrial cancers. Methods . Download the miRNA, mRNA, and lncRNA expression profile data of endometrial cancer patients from TCGA; use the "DESeq2" package of R software to identify the differential expression of miRNAs, mRNAs, and lncRNAs; construct a network of ceRNA; and perform gene ontology (GO) and Kyoto Encyclopedia of Gene and Genome (KEGG) pathway enrichment assessment on mRNAs in the network of ceRNA; string and Cytoscape 3.7.2 perform PPI assessment on target genes and TOP 10 hub gene screening; Cytoscape 3.7.2 computer program was employed for constructing the lncRNA-miRNA-TOP10 hub mRNA network diagram to determine the signal axis; StarBase database to verify the Top10 hub mRNA expression; the "survival" package in R computer program was implemented to analyze the survival rate of all genes on the lncRNA-miRNA-Top10 hub mRNA network diagram; RT-qPCR to verify the expression level of genes on the signal axis. Results . 1119 differential mRNAs, 14 differential lncRNAs, and 65 differential miRNAs were screened in TCGA; we constructed a ceRNA regulatory network composed of 5 DELs, 7 DEMs, and 90 DEGs; String combined with Cytoscape to screen out Top10 hub genes, namely: LEFTY1, LIN28A, LHX3, ST8SIA3, CEP55, FBXO32, DCN, ANGPTL1, ADRA1A, and KCNMA1; the StarBase database verification results show that ADRA1A, ANGPTL1, FBXO32, KCNMA1, and DCN are downregulated in endometrial cancer tissues; LEFTY1, LIN28A, LHX3, ST8SIA3, and CEP55 are upregulated in endometrial cancer; the constructed lncRNA-miRNA-hub Top10 mRNA network map identified CTD-2314B22, RP11-89 K21/hsa-miR-143, hsa-miR-424/LEFTY1, LIN28A, LHX3, ST8SIA3, and CEP55 signal axis; survival analysis results show that CTD-2314B22, RP11-89 K21, hsa-miR-96, hsa-miR-211, LHX3, ST8SIA3, and DCN are all related to survival; RT-qPCR results indicate CTD-2314B22, RP11-89 K21, LEFTY1, LIN28A, LHX3, ST8SIA3, and CEP55 are upregulated in endometrial cancer cells, and hsa-miR-143 and hsa-miR-424 are downregulated in endometrial cancer cells. Conclusion . From the perspective of the lncRNA-miRNA-mRNA network, our study identified CTD-2314B22, RP11-89 K21/hsa-miR-143, hsa-miR-424/LEFTY1, LIN28A, LHX3, ST8SIA3, and CEP55 signal axis, which can present considerably potent biomarkers and therapeutic targets for treating endometrial cancer.